EFL teachers’ reasons for selecting instructional materials during the COVID-19 pandemic - Suharyadi, Suharyadi; Wulyani, Anik Nunuk (citeus, 2022)
The COVID-19 pandemic has changed how teachers teach and students learn in the classroom. One of the challenges in the online teaching is that teachers are required to prepare the instructional materials for their students. This study aims at investigating the EFL teachers’ reasons for choosing the instructional materials in the time of the COVID-19 pandemic. By employing a set of questionnaires, this study collected the data from 219 English teachers from various levels of education online via the google form link. The data collection was done for one month starting from 5 May to 5 June 2020. The data were analyzed through a content analysis by identifying, grouping, and categorizing similar and different responses. The results of analysis showed that the EFL teachers have five categories of reasons in selecting the instructional materials in the time of pandemic: the instructional materials should be easy, relevant, simple, attractive, and absent from crime, pornography, and viruses. These results suggest that the EFL teachers make use of these reasons in selecting and developing the instructional materials for their students during and after the pandemic. For future textbook developers, these considerations can be used a reference to develop textbooks which accommodate students’ voices and teachers’ voices during the online teaching and learning activities.